Clinical usefulness of classification by transabdominal ultrasonography for detection of small-bowel stricture. (September 2013) - Nakano, Makoto; Oka, Shiro; Tanaka, Shinji; Aoyama, Taiki; Watari, Ikue; Hayashi, Ryohei; Miyaki, Rie; Nagai, Kenta; Sanomura, Yoji; Yoshida, Shigeto; Ueno, Yoshitaka; Chayama, Kazuaki
Abstract: Objective. To assess the clinical usefulness of transabdominal ultrasonography (TUS) for detection of small-bowel stricture. Patients and methods. Subjects were 796 patients undergoing double-balloon endoscopy (DBE), December 2003–October 2011. All underwent TUS prior to DBE. The TUS findings were classified by type as intestinal narrowing and distension at the oral side (Type A); extensive bowel wall thickening (Type B); focal bowel wall thickening (Type C) or no abnormality detected (Type D). We compared TUS findings against DBE findings with respect to small-bowel stricture, defined as failure of the enteroscope to pass through the small bowel. Results. Small-bowel stricture was detected by DBE in 11.3% (90/796) of patients. Strictures resulted from Crohn's disease ( n = 36), intestinal tuberculosis ( n = 24), malignant lymphoma ( n = 9), ischemic enteritis ( n = 6), NSAID ulcer ( n = 5), radiation enteritis ( n = 2), surgical anastomosis ( n = 2) and other abnormalities ( n = 6). Stricture was detected by TUS in 93.3% (84/90) of patients, and each such stricture fell into one of the three types of TUS abnormality. The remaining 6 strictures were detected only by DBE. DBE-identified strictures corresponded to TUS findings as follows: 100% (43/43) to Type A, 59.1% (29/49) to Type B, 14.8% (12/81) to Type C and 1% (6/623) to Type D. Correspondence between stricture and the Type A classification (vs. Types B, C and D) was significantly high, as was correspondence between stricture and Type B (vs. Types C and D). Conclusions. TUS was shown to be useful for detecting small-bowel stricture. We recommend performing TUS first when a small-bowel stricture is suspected.